Prognosis of Periodontal Disease-A Dilemma - Saurav Panda1, Rashmita Nayak1, Abhaya Chandra Das1, Manoj Kumar1, Gatha Mohanty1, Rajat Panigrahi2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Prognosis is a statistical measure of the likely outcome for an individual who undergoes periodontaltreatment. Determining prognosis at an early stage before treatment planning would help the clinician torender the periodontal treatment in confidence. The prognosis is determined by assessing the factors whichcould make the outcome of rendered treatment favorable as well as the factors which can negatively affectthe outcome. Therefore, it is crucial for the clinician to judge the prognosis with his knowledge, expertiseand patient’s compliance. This review outlines all the factors which could possibly affect the prognosis andthe clinical application of the same.